PEMBEBANAN MUT’AH DAN NAFKAH ‘IDDAH PADA PERKARA CERAI TALAK DENGAN PUTUSAN VERSTEK - Devi Yulianti; R.Agus Abikusna; Akhmad Shodikin (IAIN Syekh Nurjati Cirebon, 2020)
In filing applications for divorce for divorce at the Kuningan Religious Court, many of the petitum requests submitted by the husband are limited to terminating their marriage without being accompanied by their obligations in the form of giving mut'ah and 'iddah' living to the wife. In addition, there are some wives who have never attended trial, so the case is decided verstekally. This research aims to determine the judges 'considerations regarding the imposition of mut'ah and livelihoods of' iddah in the case of divorce talak with the verstek decision and to find out the relevance of the imposition of mut'ah and livelihood'iddah in divorce case with the verstek decision of study verdict No.1436 / Pdt.G / 2019 / PA.Kng when viewed from Article 178 paragraph (3) of the HIR. This research uses qualitative research methods, with the type of research used is field research, using several methods such as observation, interviews, and finding facts in the field related to this research. The judge's consideration in imposing mut'ah and living 'iddah is: a) juridically viewed from Law No. 1 of 1974 concerning Marriage, Compilation of Islamic Law, and Regulations of the Supreme Court of the Republic of Indonesia. b) based on Dalil al-Qur'an, the husband's obligation to give mut'ah and livelihood of ‘iddah to his ex-wife. c) based on the social circumstances of the parties. Regarding the relevance of mut'ah infliction and livelihood of iddah in divorce case with the verstek decision of study verdict No.1436 / Pdt.G / 2019 / PA.Kng when viewed from paragraph 178 verse (3) HIR, it is not considered to be contradictory as long as the matters requested by the judge are still closely related to the case being handled, in addition, in this case the judge has the freedom to use his rights, namely the ex-officio right of the judge.